(untitled) (Global Journal of Human-Social Science, 2025)
This research examines the impact of television cartoons on the socialization of youngsters in metropolitan Bangladesh. Grounded in Cultivation Theory, Social Learning Theory, and Reception Theory, it investigates the impact of sustained exposure to foreign and Hindi-dubbed cartoons on language utilization, behaviour, cognition, and health. A mixed-methods approach was employed to collect data via questionnaires from 130 parents, supplemented by qualitative case studies. Research indicates elevated levels of daily cartoon consumption (76.15%), predominantly through mobile devices, resulting in bilingual language usage (56.15%), character imitation (40%), heightened aggressiveness (36.92%), and health issues, including fast food cravings and screen addiction. Notwithstanding the acknowledgement of negative consequences, just 29% of parents impose restrictions on viewing. The research underscores an urgent necessity for age-appropriate programming, organized media literacy initiatives, and more parental engagement. It enhances comprehension of how mediated messages influence early experiences and necessitates immediate policy and educational reforms in media-saturated environments.